Atuação e interação de stakeholders no processo de implantação do turismo: um estudo no município de Sitio Novo/RN - Borges, Aylana Laissa Medeiros (2014)
The present work is a study which deals about the stakeholder approach towards the issue of tourism development in a city of Rio Grande do Norte state: Sítio Novo. As a goal, we sought to understand the stakeholders action and interaction mechanisms in the implementation process and, consequently, tourism planning in the municipality. Regarding to the methodology, the study is characterized as an exploratory and descriptive research with a qualitative approach, given the intention of trying to understand meanings and situational characteristics presented by the research subjects. The interview was the instrument used to collect information, and it was performed with 10 (ten) actors of tourism in the municipality, documents about tourism development (Proceedings of the Regional Council of Polo Agreste Trairi were analyzed Sítio Novo municipality incorporates the Polo, and the Strategic Plan for Tourism). The study shows that public actors are the majority in the destination, notes that there is a minimal involvement of civil society in actions for tourism in the municipality, highlights that representatives of the municipality participate effectively in meetings of the Regional Council of Tourism Polo Agreste Trairi, to discuss actions related to the development of the activity in the locality, and attests that local actors interviewed, mostly understand their functions regarding to tourism development, however, do not perform actions consistent with the role they have, which have as purpose the planning and development of tourism. For that matter, this paper concludes that the participation and coordination among the stakeholders of the municipality should be reconsidered in order to seek and/or propose alternatives that gather in a more adequate way the local actors, so that something more effective about the tourism development in the destination could be done